Answer:
A curve is given by y=(x-a)√(x-b) for x≥b. The gradient of the curve at A is 1.
Solution:
We need to show that the gradient of the curve at A is 1
Here given that ,
--- equation 1
Also, according to question at point A (b+1,0)
So curve at point A will, put the value of x and y
![0=(b+1-a) √((b+1-b))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9z776jp7bnh91xeuccqo26sdjgaw2d6vea.png)
0=b+1-c --- equation 2
According to multiple rule of Differentiation,
![y^(\prime)=u^(\prime) y+y^(\prime) u](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5f5rzu2mf5sc2jq0j1wtooul8nilowvia4.png)
so, we get
![{u}^(\prime)=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nuc1n4nxknk6urbqzooigths4s5v61suxf.png)
![v^(\prime)=(1)/(2) √((x-b))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8yf3ycz19yaykdj000mx64kuz3hxmovvd8.png)
![y^(\prime)=1 * √((x-b))+(x-a) * (1)/(2) √((x-b))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7xwwnipx69z75p9tk3bctumo14crro0rou.png)
By putting value of point A and putting value of eq 2 we get
![y^(\prime)=√((b+1-b))+(b+1-a) * (1)/(2) √((b+1-b))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/j9h5hhhmq8q9ax51jw85cqorclq60pcmjt.png)
![y^(\prime)=(d y)/(d x)=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rz9qp82uapxkvyzxj8twpa52ydkbfh34fj.png)
Hence proved that the gradient of the curve at A is 1.